Multilevel Regression Analysis of Age at First Birth - O. I., Adeniyi; C. O., Oyinbo-Oke; A. M., Akinrefon (Covenant Journal of Physical and Life Sciences, 2018)
Knowledge about the factors associated with age at first birth plays a major role in controlling the rate of population growth. This paper presents Hierarchical Linear Modeling known for its robustness not only in dealing with hierarchical data structure but also in its ability to explain the effects of the shared variances present in the study on the variable of interest.Â Data from 2013 Nigeria Demographic Health Survey (NDHS), collected via a hierarchically clustered sampling scheme were used. It investigated the factors that were thought to be associated with variation in age at first birth among Nigerian women were investigated. The model provided parameter estimates as well as estimates of the random effects variances at all the levels. It was observed that the average age at which a Nigerian woman gives birth to her first child without considering any factor effect is 19 years which is a teenage year. 22% and 18% in the variation of ages at first birth resides in the differences in the states and zones in the country.